2016
DOI: 10.1103/physreve.94.033113
|View full text |Cite
|
Sign up to set email alerts
|

Self-propulsion of a flapping flexible plate near the ground

Abstract: The self-propulsion of a three-dimensional flapping flexible plate near the ground is studied using an immersed boundary-lattice Boltzmann method for fluid flow and a finite-element method for plate motion. When the leading edge of the flexible plate is forced into a vertical oscillation near the ground, the entire plate moves freely due to the fluid-structure interaction. The mechanisms underlying the dynamics of the plate near the ground are elucidated. Based on the propulsive behaviors of the flapping plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…where v is the velocity, p the pressure, ρ the density of the fluid, µ the dynamic viscosity and f the body force term. The structural equation is employed to describe the plate deformation and motion (Huang & Sung 2010;Hua, Zhu & Lu 2014;Tang et al 2016):…”
Section: Physical Problem and Mathematical Formulationmentioning
confidence: 99%
“…where v is the velocity, p the pressure, ρ the density of the fluid, µ the dynamic viscosity and f the body force term. The structural equation is employed to describe the plate deformation and motion (Huang & Sung 2010;Hua, Zhu & Lu 2014;Tang et al 2016):…”
Section: Physical Problem and Mathematical Formulationmentioning
confidence: 99%
“…Some of the previous studies observed the increased power input when operating near the ground (Quinn et al 2014a;Dai et al 2016;Tang et al 2016;Park et al 2017). The body kinematics was one of the key parameters in determining the thrust and the power input (Park et al 2017).…”
Section: Fish Swimming Near the Groundmentioning
confidence: 98%
“…In the numerical study performed by Ryu et al (2016), a tethered flexible fin with a transverse heaving motion produced an enhanced thrust near the ground. Several studies adopted a self-propelled system to study the ground effect, where the swimming speed and the body kinematics are dynamically coupled (Dai et al 2016;Tang et al 2016;Park et al 2017). Dai et al (2016) and Park et al (2017) modelled a twodimensional (2D) flexible fin swimming near the ground, and the swimming speed increased with the cost of increasing input power.…”
Section: Fish Swimming Near the Groundmentioning
confidence: 99%
See 2 more Smart Citations